Constructing Accountability in Business and Human Rights: An Investigation of the Development of Foreign Direct Liability Litigation and Feasibility in Ireland - WIDDIS CAMBAY, RACHEL MARY (Trinity College Dublin. School of Law. Discipline of Law, 2021)
Constructing Accountability in Business and Human Rights: An Investigation of the Development of Foreign Direct Liability Litigation and Feasibility in Ireland RACHEL WIDDIS This thesis is situated within the field of business and human rights. The context is an on-going failure to render multinational corporations accountable for negative impacts on human rights linked to their foreign subsidiaries, and to provide effective remedy for victims. The focus in on developing legal pathways to accountability, in particular a cause of action based on the direct liability of a parent company for breach of a duty of care to those impacted by its operations. It explores the factors driving the growth of Foreign Direct Liability litigation, analyses the development of principles in comparative jurisprudence, and assesses the contribution of litigation to accountability. It reaches across human rights law, tort law, and the potential role of the Irish Constitution. Its original contribution is to relate the principles and themes synthesised from comparative Foreign Direct Liability jurisprudence to the Irish context and investigate the feasibility of similar actions in the tort of negligence against multinational corporations operating in Ireland. A model for adjudicating cases is presented based on substantive, procedural and practical aspects for Ireland.
APPROVED
Keywords: Business and Human Rights; Foreign Direct Liability Litigation